Effect of Negative Emotional Video Stimuli on Word Choice in Grade X High School - Rahman, Riki Maulida; Endang Kusmaryani, Rosita; Ayriza, Yulia; Vaida, Sebastian (IJORER : International Journal of Recent Educational Research, 2025)
Objective: Emotional problems that arise in adolescents are often caused by situations within their family or neighborhood, but physical health and the influence of visual media or movie shows can also affect the emotional state of adolescents. This study aims to determine the impact of negatively charged videos on emotions in word choice This research uses a quantitative approach with an experimental method of the true experimental type. The sampling technique is simple random sampling, which is a technique where each member of the population has the same opportunity to become a research sample. The difference test used is the Mann-Whitney test because the data is an independent sample. The results showed that P = 0.000 ≤ α (0.05), then H0 was rejected, or which means that there was a difference in the number of negative word scores between the control group and the experimental group in class X students of SMA Negeri 1 Ngaglik. By rejecting H0, the study provides evidence of a significant difference in word choice between the group given the negative emotion stimulus and the control group.